Superparamagnetic core-shell nanoparticles for biomedical applications - Suk, Fun Chin; Swaminatha Iyer, K.; Raston, Colin L. (IEEE, 2011)
Superparamagnetic magnetite (Fe3O4) nanoparticles have been widely studied for various scientific and technological applications such as magnetic storage media, contrast agents for magnetic resonance imaging (MRI), biolabelling and separation of biomolecules, and magnetic targetted drug delivery. In the absence of surface coating, Fe3O4 nanoparticles tend to aggregate due to the Van der Waals forces coupled with the magnetic dipole-dipole attractions between the particles. In order to successfully prepare stable magnetite dispersions, any attractive forces between the nanoparticles must be overcome. In this study, magnetite nanoparticles have been prepared by chemical precipitation method. Gold (Au) and silver (Ag) are ideal coating for Fe3O4 nanoparticles due to their high chemical stability, biocompatibility, and their affinity for binding to amine/thiol terminal groups of organic molecules. In addition these coatings also render the Fe3O4 nanoparticles with plasmonic properties.